Transforming Religious Learning with Macromedia Flash 8: Improving Students' Understanding of the Material on Faith in the Apostles - Melinda, Siska; Feizi , Farokh; Monfared , Parisa Naeimian (Journal of Educational Technology and Learning Creativity, 2024)
Purpose of the study: This study aims to determine the effect of using Macromedia Flash 8 on student learning outcomes in the subject of Islamic Religious Education, material on Faith in the Apostles for Class XI at Aisyiyah 1 High School, Palembang. Methodology: This research employed a quantitative, quasi-experimental approach with two classes of 35 students each from XI Aisyiyah 1 High School, Palembang, divided into experimental and control groups. Instruments included written tests and Likert scale questionnaires, with Macromedia Flash 8 as the learning media. Data were analyzed using t-tests and descriptive analysis via SPSS to measure students' perceptions. Main Findings: The study found that Macromedia Flash 8 significantly improves student understanding of the concept of faith in the Apostles compared to conventional methods. The experimental group using Macromedia Flash 8 scored an average of 85.20, significantly higher than the control group’s 78.50 (p = 0.004). Additionally, students showed positive perceptions of this media, with 82.9% rating it as "Positive" or "Very Positive." These results indicate that Macromedia Flash 8 not only enhances comprehension but also boosts student engagement and satisfaction, making it an effective tool for improving learning outcomes in religious education.. Novelty/Originality of this study: This study demonstrates that Macromedia Flash 8 significantly enhances student understanding in religious education, offering a technology-based approach to improve learning quality. It contributes to the development of interactive learning media in religious education, showcasing the potential of digital tools to elevate engagement and comprehension.